Territorial and Sustainable Healthy Diets. Issue 2 (December 2020) - Hachem, Fatima; Vanham, Davy; Moreno, Luis A.
The rapid changes that societies have gone through in the last few decades have led to the increase in the prevalence of malnutrition in all its forms and to the degradation of natural resources and the environment. The change in the dietary habits and production systems are responsible for much of this change. Some territorial diets have been shown as potentially capable of reversing these trends by positively contributing to the health of people and the environment such as the Mediterranean Diet and the New Nordic Diet. In this paper, we review the contribution of these 2 diets to health and nutrition and to environmental, sociocultural, and economic sustainability proposing pertinent indicators. Learning from a culturally established diet and a constructed one, tradeoff could be reached to ensure better health and sustainability outcomes. Strong factors for achieving this goal lie in building on the sociocultural appropriation of diets, having the proper tools and indicators, investing in cross-sector collaboration and policy coherence, and having the necessary political support to push the agenda of sustainability forward.